Improved Folch Method for Liver-Fat Quantification - Mopuri, Ramgopal; Kalyesubula, Mugagga; Rosov, Alexander; Edery, Nir; Moallem, Uzi; Dvir, Hay (Frontiers in Veterinary Science, 2021)
Fatty liver represents a significant metabolic pathology of excess intrahepatic fat in domestic animals and humans. Quantification of hepatic-fat content is therefore essential for diagnosis and investigation of liver and metabolic disease. However, the reproducibility of hepatic steatosis analysis is often low due to subjective and technical factors. We hypothesized that improvement in tissue-lipids extraction efficiency would contribute to the accuracy and precision of liver-fat determination. To test it, we investigated the effect of standardized tissue sonication on liver-fat quantification by the Folch method in sheep. Liver samples from grownup lambs of lean (n=16) and fatty (n=15) livers, and from pregnant ewes (n=6) who died from pregnancy toxemia (PT), were used for hepatic-fat content determination with or without tissue sonication. In the grown lambs, an average hepatic-fat content of 6.6% was determined in sonicated compared to 5.1% in non-sonicated specimens (P = 0.0002). Similarly, in ewes with PT, an average of 12.5 % was determined with sonication compared to 10.8% without it (P = 0.0006), and the reproducibility was higher with sonication (CV of 3.1% vs. 6.1%, respectively). Thus, tissue sonication improved the efficiency of liver-lipids extraction and was significant to the accuracy and precision of hepatic-fat determination. Enzymatic quantification of triglycerides was moderately correlated with the results obtained gravimetrically (r= 0.632, P < 0.005). The reported data provide reliable reference values for pregnancy toxemic sheep. The significant improvement in liver-fat quantification observed with the reported revised protocol is likely applicable to most mammals and humans.